Derivasi Verba dalam Bahasa Lampung melalui Pendekatan Linguistik Komputasional - Dewi Ratnaningsih; Ifan Iskandar; Miftahulkhairah Anwar (Sienna, 2025)
This study presents a comprehensive analysis of verbal derivation in Lampung Language Dialects A and O, employing a computational linguistic approach to identify affixation patterns, morphophonemic processes, and the semantic and syntactic contributions of affixes. Verbal data were categorized according to prefixes, infixes, suffixes, and circumfixes. The findings show that both dialects exhibit highly consistent verbal derivation systems. The nasal prefix (N-) is the most productive, marking active transitivity and causativity, with identical nasal assimilation processes in both dialects (b/p → m-, d/t → n-, k/g → ng-, s/c/j → ny-, vowels → nge-/ng-). Other prefixes, such as di-, consistently indicate passivization, while be-/ber- and te-/ti- signal reciprocal/stative verbs and unintentional passives. Major suffixes (-ken, -ko, -an, -kon) function as causative, applicative, or result markers, whereas infixes (-el-, -em-, -en-, -er-) primarily modify phonology or add semantic nuance. Dialect comparison confirms strong structural similarity, with minor phonetic variations, such as object suffixes (-ni/-na in Dialect A vs. -no in Dialect O) and less productive affixes (bu- in Dialect A, per- in Dialect O). Formalization of derivation rules in Python successfully predicted most derived forms, although further refinement is needed for nasal assimilation on vowel-initial stems and vowel deletion in suffixation. This study underscores the fundamental similarity in Lampung verbal morphology and opens opportunities for computational linguistic applications, including morphological analyzers, translation tools, and language learning systems, which are vital for the preservation of regional languages. The results also contribute to a deeper understanding of Austronesian morphological typology.